(3EOGQI GdGUhd GdQCSeGdjI (B((3c(B23) /s - (3eMeO, YGOd eHQhcs ((3GdbGgQI(B: s (3eWHYI eQcR GdJYdje GdeaJhM(B, s)
(3WHjYI GdGUhd GdQGSeGdjI, eMOOGJ EOGQI GdGUhd GdQGSeGdjI, JMOjO GdGMJjGLGJ ef GdGUhd GdQGSeGdjI, JNWjW hQbGHI GdfabGJ GdGSJKeGQjI GdehGRfI GdQGSeGdjI , eUGOQ Jehjd GdGUhd GdQCSeGdjI , GSJNOGeGJ eUGOQ Jehjd GdGUhd GdQGSeGdjI, fXe GOGQI JfajP GdeTQhYGJ GdQCSeGdjI, GdGSGdjH GdJMdjdjI dGfJGLjI hQHMjI GdGUhd GdQGSeGdjI, GdbQGQGJ GdNGUI HGOGQI GdGUhd GdQGSeGdjI s
(3eQGLY U U(B.291-293s
Keywords: (3GdQCSeGdjIs